(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article provides information on the study of Alisher Navoi’s life and work in the secondary and higher education system, and the place of Navoi’s figure in the life of our society. Opinions were expressed about the education of the great thinker.